2014
DOI: 10.1002/chem.201403768
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Asymmetric Allylic Substitution of Free Alcohols: An Enantioselective Approach to Chiral Chromans with Quaternary Stereocenters for the Synthesis of Vitamin E and Analogues

Abstract: The enantioselective synthesis of α- and γ-tocopherol (the most biologically active members of vitamin E family) and analogues has been accomplished employing a new enantioselective gold catalyzed intramolecular allylic alkylation reaction followed by an olefin cross-metathesis as key steps. The methodology proved to be applicable to different olefins highlighting its potential for the synthesis of diverse libraries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…For the synthesis of the chiral chroman motifs, a variety of enantioselective approaches have been described . For years, a great deal of attention has focused on asymmetric synthesis that relies on transition metal-catalyzed Wacker-type or allylic substitution processes . However, the construction of chiral chroman frameworks via direct inert C–H oxidation strategy has not been reported, yet .…”
mentioning
confidence: 99%
“…For the synthesis of the chiral chroman motifs, a variety of enantioselective approaches have been described . For years, a great deal of attention has focused on asymmetric synthesis that relies on transition metal-catalyzed Wacker-type or allylic substitution processes . However, the construction of chiral chroman frameworks via direct inert C–H oxidation strategy has not been reported, yet .…”
mentioning
confidence: 99%
“…Bandini et al demonstrated the feasibility of a cascade reaction, with gold-catalyzed alkyne hydroamination followed by the typical allylic alcohol activation [77]. Finally, the enantioselective total synthesis of α-and γ-tocopherol (vitamin E family members) was realized by Rueping et al in 2014, utilizing this strategy [78]. In many of these cases, the starting olefin geometry of the substrate is important, with the other isomer generally giving reduced yield and ee.…”
Section: Intramolecular Cyclizationsmentioning
confidence: 97%
“…Gold‐catalyzed asymmetric dehydrative hydroalkoxylation of allylic alcohol ( E )‐ 229 for preparation of chiral vinyl chroman 230 was reported by Rueping and co‐workers in 2014 (Scheme ) . By treating the substrates with a 1:2 catalytic mixture of [( R )‐dm‐segphos(AuCl) 2 ] and AgOTf in toluene at room temperature, the desired multisubstituted vinyl chromans 230 were obtained in moderate to high yields with good ee values.…”
Section: Cyclization Of C−c Multiple Bonds With Tethered Nucleophilesmentioning
confidence: 99%